On the Complexity of Optimising Variants of Phylogenetic Diversity on Phylogenetic Networks - Bordewich, Magnus; Semple, Charles; Wicke, Kristina (Theoretical Computer Science, 2022)
Phylogenetic Diversity (PD) is a prominent quantitative measure of the biodiversity of a collection of present-day species (taxa). This measure is based on the evolutionary distance among the species in the collection. Loosely speaking, if T is a rooted phylogenetic tree whose leaf set X represents a set of species and whose edges have real-valued lengths (weights), then the PD score of a subset S of X is the sum of the weights of the edges of the minimal subtree of T connecting the species in S. In this paper, we dene several natural variants of the PD score for a subset of taxa which are related by a known rooted phylogenetic network. Under these variants, we explore, for a positive integer k, the computational complexity of determining the maximum PD score over all subsets of taxa of size k when the input is restricted to dierent classes of rooted phylogenetic networks.
EPrint Processing Status: Full text deposited in DRO